2021
DOI: 10.1186/s12987-021-00257-0
|View full text |Cite
|
Sign up to set email alerts
|

Brain pharmacokinetics of two BBB penetrating bispecific antibodies of different size

Abstract: Background Transferrin receptor (TfR1) mediated enhanced brain delivery of antibodies have been studied extensively in preclinical settings. However, the brain pharmacokinetics, i.e. brain entry, distribution and elimination are still not fully understood for this class of antibodies. The overall aim of the study was to compare the brain pharmacokinetics of two BBB-penetrating bispecific antibodies of different size (210 vs 58 kDa). Specifically, we wanted to investigate if the faster systemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 49 publications
11
49
0
Order By: Relevance
“…This confirms that TfR1 mediated transport is a robust strategy for enhancing brain delivery of affibody molecules (37). Di-scFv3D6-8D3 binds monovalently to mTfR1 (50), which has been reported to increase brain uptake (10,51).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…This confirms that TfR1 mediated transport is a robust strategy for enhancing brain delivery of affibody molecules (37). Di-scFv3D6-8D3 binds monovalently to mTfR1 (50), which has been reported to increase brain uptake (10,51).…”
Section: Discussionsupporting
confidence: 67%
“…Di-scFv3D6-8D3 binds monovalently to mTfR1 (50), which has been reported to increase brain uptake (10,51). We have previously shown that di-scFv3D6-8D3 displayed higher brain parenchyma-to-capillary ratio compared to the 210 kDa bivalent IgG-based antibody, mAb3D6-scFv8D3, potentially due to the monovalent TfR1 interaction of di-scFv3D6-8D3 (37). The impact of TfR1 affinity on therapeutic antibodies has also been studied, where a moderate affinity of 50 nM-100 nM was found optimal for brain delivery (52).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although their slow pharmacokinetics is a clear draw-back, their ability to detect Aβ beyond amyloid is interesting. Smaller bispecific formats appear to show more favorable and PET compatible pharmacokinetics than large antibody-like formats (35,92,93). Further, bispecific antibodies have also been labelled with the clinically preferred radionuclide 18 F (94).…”
Section: Futurementioning
confidence: 99%